2019
DOI: 10.1177/0300060518797000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of intrathecal bupivacaine alone and bupivacaine combined with dexmedetomidine in cesarean section using spinal anesthesia: a meta-analysis

Abstract: Objective This meta-analysis was performed to evaluate the effect of spinal anesthesia (SA) using bupivacaine combined with dexmedetomidine (DEX) in cesarean section, analyze the adverse drug reactions induced by this mixture, and provide a reference for rational drug use. Methods Randomized controlled trials were obtained from the PubMed, Cochrane Library, and Embase databases. The primary outcome measure was the time to the highest sensory block level (min), and the secondary outcome measure was adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). Zhou et al found that dexmedetomidine can reduce the traumatic stress response and immune suppression caused by surgery and has a protective effect on the spinal cord in spinal surgery (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…7 There has been growing attention in using local anesthetic (LA) adjuvants to accelerate the onset of action and prolong the analgesic effect of LA. 14,19 Multiple studies have shown that using dexmedetomidine as an adjuvant to LA in peripheral nerve techniques enhance the onset of action, increase the duration of analgesia, and decrease postoperative analgesic intake. 20,21 As regard FICB, Sabra, et al 15 added dexmedetomidine to ropivacaine in order to study its postoperative analgesic effect in hip arthroplasty, they reported that combining ropivacaine and dexmedetomidine significantly decrease pain scores and 24 hours analgesic requirement as opposed to solely using ropivacaine.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…It has been added to bupivacaine to decrease the onset time for sensory block during spinal, epidural, and brachial plexus blocks with good results. 12,13,14 Although few randomized studies investigated the postoperative effect of dexmedetomidine as an adjuvant to LA in supra-inguinal FICB, there is little knowledge about its preoperative effect, and to our knowledge, no study has been investigated the effect of adding dexmedetomidine to bupivacaine in FICB as regard facilitating spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal anesthesia is the most common and safe anesthetic method for patients with cesarean section 1,2. Among factors that affect the decision of anesthesiologist to perform spinal anesthesia severity of spinal anesthesia and the experience of anesthetist who carries out spinal anesthesia make sense 3.…”
Section: Introductionmentioning
confidence: 99%